Whose Crisis? COVID-19 Explored through Arts and Cultural Practices of African Communities - Mia Perry; Dane Mathendele Armstrong; Bosco Exson Chinkonda; Richard Kagolobya; Rebecca Nthogo Lekoko; George Olusola Ajibade (Journal of Open Humanities Data)
The “Whose Crisis?” project is in response to a continually evolving global health pandemic, COVID-19. In this context, the dominant discourses have been generated in the Global North, overwhelmingly by a minority of wealthy and powerful authors, reflecting narrowly on a crisis that, while impacting the whole world, is experienced in vastly different ways. This article frames and contextualises data from this project through an introduction to the background, contexts, and methods of a project designed to reflect the lived experiences of, perspectives on, and responses to COVID-19 in vulnerable communities across sub-Saharan Africa. The project has been carried out by a large team of collaborators who prioritise the lived experiences, customs, and needs of the communities engaged through a culturally responsive and arts-based research approach. The article points to the methodological implications of arts-based research to explore plural perspectives in participatory ways, and the socio-political possibilities of amplifying the voices of under-represented and under-served communities in Africa, in terms of global health in a pandemic context.